Impregnated adhesive for pressing decorative paper on board surface and preparation method thereof
By adding glutinous rice starch, plant oil acid and modified nanomaterials to the addylidaldehyde resin, the problem of brittleness and stability of existing pectin is solved, improved the toughness, wear resistance and water resistance of impregnated glue, optimized the impregnated decorative paper Pastening process.
Patent Information
- Application Number
- CN202410768661.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-06-14
AI Technical Summary
The existing melamine formaldehyde resins have problems in application, such as high brittleness, poor hydrophobic properties and poor stability, and the addition of flexible long-chain polymers will affect the permeability and impregnation time of the resin.
Melamine formaldehyde resin is used as the matrix, with glutinous rice starch, vegetable oleic acid and composite additives, including modified nano-silica and modified nano-titanium dioxide, to improve the toughness, wear resistance and water resistance of the impregnated glue through modification treatment.
The prepared impregnating glue has good toughness, wear resistance and water resistance, is stable in storage, has a high pre-curing value, and relatively reduces the pressing time, and is suitable for the pressing process of decorative paper on the board surface.
Smart Images

Figure BDA0004893439470000081 
Figure BDA0004893439470000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to an impregnated adhesive for pressing decorative paper on a board surface and a preparation method thereof. Background Art
[0002] Impregnated film paper veneer is a veneer base paper that is soaked in impregnating resin, dried and dehydrated to obtain an impregnated film paper with a certain pre-curing degree, glue amount and volatile content. The impregnated paper is then subjected to high temperature to remove the water produced in the cross-linking process, and is further hot-pressed with the wood substrate. The impregnated paper and the wood-based panel substrate are glued together to obtain an impregnated veneer wood-based panel, which is usually used in building decoration materials. At present, commonly used impregnation adhesives include melamine formaldehyde resin, urea-formaldehyde resin and phenolic resin. Among them, melamine formaldehyde resin has the advantages of simple synthesis process, fast curing, strong adhesion, light color, scratch resistance and high temperature resistance. It occupies the main share of adhesives for impregnated film paper and is widely used in outdoor board coatings, wood floor decorative layers and veneer products.
[0003] During the impregnation, the melamine formaldehyde resin prepolymer is impregnated into the pores of the paper fiber. After drying, the melamine formaldehyde resin is further polycondensed to partially solidify, forming an impregnated paper with a certain degree of pre-curing, which is then hot-pressed with the board and cross-linked until fully cured, finally forming an infusible melamine formaldehyde resin with a three-dimensional network structure. However, melamine formaldehyde resin contains a large number of rigid triazine rings, imino groups and hydroxymethyl groups, which make it brittle, poor hydrophobicity and poor stability, so it needs to be modified when used. Currently, flexible long-chain polymers are added to melamine formaldehyde resin to enhance toughness and improve the folding resistance of melamine formaldehyde resin impregnated paper. However, in actual application, the flexible long-chain polymers will increase the viscosity of the resin, affect the permeability of the resin, and cause problems such as long impregnation time and uneven impregnation, thereby affecting the appearance performance of the impregnated film paper veneer and reducing product quality. In addition, the flexibility of melamine formaldehyde resin is improved by reducing the cross-linking density of melamine formaldehyde resin and extending its flexible chain length. However, the reduction in cross-linking density means that the rigid structure of the triazine ring in the resin is dispersed, so the surface rigidity and wear resistance of the melamine formaldehyde resin will be affected to varying degrees. Summary of the invention
[0004] In order to solve the deficiencies mentioned in the above-mentioned background technology, the purpose of the present invention is to provide an impregnating glue for pressing decorative paper on a board surface and a preparation method thereof. The impregnating glue is based on melamine formaldehyde resin, and glutinous rice starch, vegetable oil acid and composite additives are added. The prepared impregnating glue has good toughness, wear resistance and water resistance, and is stable in storage, has a high pre-curing value, and the pressing time is relatively reduced.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] An impregnating adhesive for pressing decorative paper on a board surface comprises the following raw materials in parts by weight: 60 to 75 parts of melamine, 50 to 80 parts of formaldehyde, 5 to 15 parts of glutinous rice starch, 1 to 3 parts of vegetable oleic acid, 10 to 20 parts of composite additives, and 30 to 45 parts of deionized water;
[0007] The composite additive is a mixture of modified nano silicon dioxide and modified nano titanium dioxide in a mass ratio of 3 to 6:1; the modified nano silicon dioxide is amino nano silicon dioxide grafted with a carboxyl-terminated oligoester toughening agent; and the modified nano titanium dioxide is carboxylated nano titanium dioxide grafted with neodecanoic acid glycidyl ester.
[0008] Preferably, the preparation method of the modified nano-silicon dioxide comprises the following steps:
[0009] A. Take nano-silica and disperse it in toluene by ultrasonic, pass nitrogen through the reaction, add γ-aminopropyltriethoxysilane and triethylamine, stir and mix at 70-90° C., reflux for 9-12 hours, and after the reaction is completed, filter, wash and dry to prepare amino-modified nano-silica;
[0010] B. Take amino nano-silica and dispers it in N,N-dimethylformamide by ultrasonic dispersion, add terminal carboxyl oligoester toughening agent, reflux at 90-115°C for 5-8h, wash and dry after the reaction is completed, and prepare modified nano-silica.
[0011] Preferably, in step A, the mass ratio of nano-titanium dioxide to γ-aminopropyltriethoxysilane is 3-6:7-10.
[0012] Preferably, in step B, the mass ratio of the amino-modified nano-silica to the carboxyl-terminated oligoester toughening agent is 1:1.5-5.
[0013] Preferably, the preparation method of the carboxyl-terminated oligoester toughening agent in step B comprises the following steps:
[0014] B1, take phenylphosphoryl dichloride and diethylene glycol in a reactor filled with tetrahydrofuran, stir and mix at room temperature, then add triethylamine to react for 4 to 8 hours, remove the hydrogen chloride produced by the reaction, and after the reaction is completed, filter, rotary evaporate, and dry to prepare a toughening agent intermediate;
[0015] B2. Take the toughening agent intermediate and glutaric acid in a reactor, place it at 120-135° C. and stir to react for 6-7 hours. After the reaction is completed, place it in a vacuum oven to dry, and prepare a carboxyl-terminated oligoester toughening agent.
[0016] Preferably, in the step B1, the mass ratio of phenylphosphoryl dichloride, diethylene glycol and triethylamine is 1:1.1-1.5:1-1.2; and in the step B2, the mass ratio of the toughening agent intermediate and glutaric acid is 1.9-2.5:1.
[0017] Preferably, the preparation method of the modified nano titanium dioxide comprises the following steps:
[0018] (1) γ-aminopropyltriethoxysilane and succinic anhydride are placed in N,N-dimethylformamide and stirred at 70-95° C. for 2-4 hours to form a mixed solution, nano-titanium dioxide is dispersed in N,N-dimethylformamide, deionized water is added after ultrasonic treatment, and then added to the mixed solution and stirred for 4-5 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to prepare carboxylated nano-titanium dioxide;
[0019] (2) Dissolve carboxylated nano-titanium dioxide in butyl acetate and disperse by ultrasonication, add triphenylphosphine and hydroquinone, stir and mix at 95-110° C., then add glycidyl neodecanoate to react for 10-14 hours. After the reaction is completed, filter, wash and dry to prepare modified nano-titanium dioxide.
[0020] Preferably, in step (1), the mass ratio of γ-aminopropyltriethoxysilane, succinic anhydride and nano-titanium dioxide is 2-2.5:0.5-1:2-3.
[0021] Preferably, in step (2), the mass ratio of carboxylated nano-titanium dioxide to glycidyl neodecanoate is 1:1.2-3.
[0022] Preferably, the method for preparing the impregnated adhesive for pressing decorative paper on a board surface as described above comprises the following steps:
[0023] S1. Weigh each raw material by weight, mix formaldehyde and deionized water to obtain a mixture A;
[0024] S2, adjusting the pH value of the mixture A to 8-9.5, raising the temperature to 70-85° C. and keeping the temperature for 20-30 min, adding melamine, stirring and mixing for 20-30 min, and obtaining a mixture B;
[0025] S3, adding glutinous rice starch, vegetable oil acid and composite additives into mixture B, stirring and mixing for 2 to 4 hours, and preparing the impregnating adhesive for pressing the decorative paper on the board surface.
[0026] Beneficial effects of the present invention:
[0027] The present invention utilizes phenylphosphoryl dichloride and diethylene glycol to undergo a substitution reaction to synthesize a toughening agent intermediate, and then utilizes the toughening agent intermediate to undergo a polyesterification reaction with glutaric acid to synthesize a carboxyl-terminated oligoester toughening agent. The introduced phosphorus element not only enables it to have a toughening effect, but also can improve the flame retardant properties of the impregnated adhesive to a certain extent. The present invention utilizes γ-aminopropyltriethoxysilane to modify nano-silica, which is beneficial to the dispersion of nano-silica to obtain amino-type nano-silica, and then the amino-type nano-silica is subjected to an amidation reaction with the carboxyl-terminated oligoester toughening agent to prepare modified nano-silica, which has an excellent toughening effect while avoiding affecting the wear resistance of the impregnated adhesive. At the same time, the strong combination of the two through chemical bonds is beneficial to improving storage stability. In addition, the present invention utilizes γ-aminopropyltriethoxysilane and succinic anhydride to perform carboxyl modification on nano-titanium dioxide, which is an important inorganic violet. The external shielding agent has good weather resistance and heat resistance, and due to its special photocatalytic activity, it has strong antibacterial and bactericidal ability after absorbing ultraviolet light energy. The carboxylated nano titanium dioxide is mixed with neodecanoic acid glycidyl ester, and the carboxyl group on the surface of the nano titanium dioxide and the epoxy group on the surface of the neodecanoic acid glycidyl ester undergo a ring-opening reaction under the action of the catalyst, thereby introducing tertiary carbonic acid hydrophobic groups on the surface of the nano titanium dioxide to improve the water resistance of the impregnating glue. At the same time, neodecanoic acid glycidyl ester has good thermal stability, light stability and viscosity reduction function, which can reduce the viscosity of the impregnating glue and avoid affecting the permeability of the impregnating glue.
[0028] The present invention uses melamine formaldehyde resin as a matrix, adds glutinous rice starch, vegetable oil acid and composite additives, and the prepared impregnated glue has good toughness, wear resistance and water resistance, and is stable in storage, has a high pre-curing value, and relatively reduces the pressing time. The pressing process of the impregnated decorative paper can be reduced to within 20 seconds in the application of medium-density fiberboard, and reduced to within 150 seconds for multilayer boards. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Embodiment 1 A method for preparing a carboxyl-terminated oligoester toughening agent comprises the following steps:
[0031] B1, take 5g of phenylphosphoryl dichloride and 6.2g of diethylene glycol in a reactor containing 100mL of tetrahydrofuran, stir and mix at room temperature, then add 5g of triethylamine to react for 6h, remove the hydrogen chloride produced by the reaction, filter after the reaction is completed, rotary evaporate, and dry to prepare a toughening agent intermediate;
[0032] B2. Take 5.4 g of the toughening agent intermediate and 2.7 g of glutaric acid into a reactor, place it at 125° C. and stir to react for 7 hours. After the reaction is completed, place it in a vacuum oven to dry to prepare a carboxyl-terminated oligoester toughening agent.
[0033] Embodiment 2 A method for preparing modified nano-silicon dioxide comprises the following steps:
[0034] A. Take 5.7g of nano-silica and dissolve it in 100mL of toluene by ultrasonic dispersion, pass nitrogen through the reaction, add 8.2g of γ-aminopropyltriethoxysilane and 1.2g of triethylamine, stir and mix at 80°C, reflux for 12h, and after the reaction is completed, filter, wash and dry to prepare amino-modified nano-silica;
[0035] B. Take 5.2g of amino-modified nano-silica and dispers it in 100mL of N,N-dimethylformamide by ultrasonic dispersion, add 10.4g of terminal carboxyl oligoester toughening agent, reflux at 105°C for 6h, wash and dry after the reaction is completed, and prepare modified nano-silica.
[0036] Embodiment 3 A method for preparing modified nano titanium dioxide comprises the following steps:
[0037] (1) 5 g of γ-aminopropyltriethoxysilane and 1.7 g of succinic anhydride were dissolved in 100 mL of N,N-dimethylformamide and stirred at 80° C. for 4 h to form a mixed solution, 5 g of nano-titanium dioxide was dispersed in 100 mL of N,N-dimethylformamide, 10 mL of deionized water was added after ultrasonic treatment, and then added to the mixed solution and stirred for 5 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to prepare carboxylated nano-titanium dioxide;
[0038] (2) Take 5 g of carboxylated nano-titanium dioxide and dissolve it in 50 mL of butyl acetate and disperse it by ultrasonication, add 0.007 g of triphenylphosphine and 0.001 g of hydroquinone, stir and mix at 110°C, then add 6.3 g of neodecanoic acid glycidyl ester and react for 12 hours. After the reaction is completed, filter, wash and dry to prepare modified nano-titanium dioxide.
[0039] Example 4: An impregnating adhesive for pressing decorative paper on a board surface comprises the following raw materials in parts by weight: 60 parts of melamine, 50 parts of formaldehyde, 7 parts of glutinous rice starch, 1 part of vegetable oleic acid, 11 parts of composite additives, and 32 parts of deionized water, wherein the composite additive is a mixture of modified nano-silicon dioxide and modified nano-titanium dioxide in a mass ratio of 3:1.
[0040] The method for preparing the impregnated adhesive for pressing decorative paper on the board surface comprises the following steps:
[0041] S1. Weigh each raw material by weight, mix formaldehyde and deionized water to obtain a mixture A;
[0042] S2, adding 30% sodium hydroxide solution to adjust the pH value of mixture A to 9, raising the temperature to 80° C. and keeping the temperature for 20 min, adding melamine, stirring and mixing for 30 min, and obtaining mixture B;
[0043] S3. Add glutinous rice starch, vegetable oleic acid and composite additives to mixture B, and stir and mix for 4 hours to prepare the impregnating adhesive for pressing the decorative paper on the board surface.
[0044] Example 5: An impregnating adhesive for pressing decorative paper on a board surface comprises the following raw materials in parts by weight: 68 parts of melamine, 72 parts of formaldehyde, 10 parts of glutinous rice starch, 2 parts of vegetable oleic acid, 14 parts of a composite additive, and 40 parts of deionized water, wherein the composite additive is a mixture of modified nano-silicon dioxide and modified nano-titanium dioxide in a mass ratio of 5:1.
[0045] The preparation method of the impregnated adhesive for pressing the decorative paper on the board surface is the same as that in Example 4.
[0046] Example 6: An impregnating adhesive for pressing decorative paper on a board surface comprises the following raw materials in parts by weight: 75 parts of melamine, 77 parts of formaldehyde, 15 parts of glutinous rice starch, 3 parts of vegetable oleic acid, 20 parts of a composite additive, and 45 parts of deionized water, wherein the composite additive is a mixture of modified nano-silicon dioxide and modified nano-titanium dioxide in a mass ratio of 6:1.
[0047] The preparation method of the impregnated adhesive for pressing the decorative paper on the board surface is the same as that in Example 4.
[0048] Comparative Example 1 A method for preparing modified nano titanium dioxide comprises the following steps:
[0049] Take 5g of γ-aminopropyltriethoxysilane and 1.7g of succinic anhydride in 100mL of N,N-dimethylformamide, stir at 80°C for 4h to form a mixed solution, take 5g of nano-titanium dioxide and disperse it in 100mL of N,N-dimethylformamide, add 10mL of deionized water after ultrasonic treatment, and then add it to the mixed solution and continue stirring for 5h. After the reaction is completed, centrifuge, wash and dry to prepare modified nano-titanium dioxide.
[0050] Comparative Example 2 A method for preparing modified nano-silicon dioxide comprises the following steps:
[0051] Take 5.7g of nano-silica and dispers it ultrasonically in 100mL of toluene. Pass nitrogen through the reaction. Add 8.2g of γ-aminopropyltriethoxysilane and 1.2g of triethylamine. Stir and mix at 80°C. Reflux for 12h. After the reaction is completed, filter, wash and dry to prepare modified nano-silica.
[0052] Comparative Example 3: An impregnating adhesive for pressing decorative paper on a board surface comprises the following raw materials in parts by weight: 75 parts of melamine, 77 parts of formaldehyde, 15 parts of glutinous rice starch, 3 parts of vegetable oil acid, 20 parts of a terminal carboxyl oligoester toughening agent, and 45 parts of deionized water.
[0053] The preparation method of the impregnated adhesive for pressing the decorative paper on the board surface is the same as that in Example 4.
[0054] Comparative Example 4: An impregnating adhesive for pressing decorative paper on a board surface comprises the following raw materials in parts by weight: 75 parts of melamine, 77 parts of formaldehyde, 15 parts of glutinous rice starch, 3 parts of vegetable oleic acid, 20 parts of a composite additive, and 45 parts of deionized water, wherein the composite additive is prepared by mixing the modified nano-silicon dioxide prepared in Example 2 with the modified nano-titanium dioxide prepared in Comparative Example 1 in a mass ratio of 6:1.
[0055] The preparation method of the impregnated adhesive for pressing the decorative paper on the board surface is the same as that in Example 4.
[0056] Comparative Example 5: An impregnating adhesive for pressing decorative paper on a board surface comprises the following raw materials in parts by weight: 75 parts of melamine, 77 parts of formaldehyde, 15 parts of glutinous rice starch, 3 parts of vegetable oleic acid, 20 parts of a composite additive, and 45 parts of deionized water, wherein the composite additive is prepared by mixing the modified nano-silicon dioxide prepared in Comparative Example 2 and the modified nano-titanium dioxide prepared in Example 3 in a mass ratio of 6:1.
[0057] The preparation method of the impregnated adhesive for pressing the decorative paper on the board surface is the same as that in Example 4.
[0058] Performance Testing
[0059] a. The impregnated glue prepared in Examples 4-6 was tested with reference to GB / T 14074-2017, and the data results are shown in Table 1.
[0060] Table 1 Test results of sample performance
[0061]
[0062] It can be seen from the data in Table 1 that the impregnated glue prepared in the embodiment of the present invention has a clear and transparent appearance without precipitation, and has good curing time, solid content, water resistance and storage stability.
[0063] b. The impregnated wood grain paper prepared in Examples 4-6 and Comparative Examples 3-5 was impregnated with the impregnated glue, and the impregnated paper veneer artificial board was obtained by hot pressing veneer under the conditions of hot pressing temperature of 180-200°C, hot pressing unit pressure of 2-3MPa, hot pressing closing time of 20-40s, and the following performance tests were performed:
[0064] (1) Pre-curing degree test: After weighing the sample, completely immerse it in a digital constant temperature water bath at 40±2°C. After soaking for 20 minutes, take it out and hang it at room temperature for 15 minutes. Put it in a 160±2°C constant temperature drying oven for 10 minutes. Take out the sample and put it in a dryer to cool to room temperature and then weigh it: pre-curing degree = (mass of impregnated paper after soaking and drying - mass of base paper) / mass of base paper × 100%. The data results are shown in Table 2.
[0065] (2) Abrasion resistance and scratch resistance test: The test was carried out in accordance with GB / T 17567-2013, and the data results are shown in Table 2.
[0066] (3) Flexibility test: Flexibility mainly refers to the degree of bending under force. The greater the bending, the better the toughness. The curling radius of the impregnated paper is used as the flexibility parameter. The data results are shown in Table 2.
[0067] (4) Contact angle test: The test sample paper was selected as the veneer silver paper, and the instrument was used to select the ellipse method (20° is less than the contact angle to be measured <120°) for testing. The data results are shown in Table 2.
[0068] (5) Flame retardant performance test: The limiting oxygen index was tested according to GB / T 2046-2009. The sample size was 100 mm × 6.5 mm × 3.2 mm. The data results are shown in Table 2.
[0069] Table 2 Test results of sample performance
[0070]
[0071] From the data in Table 2, it can be seen that the film paper prepared in Examples 4-6 of the present invention has a high pre-curing degree, excellent wear resistance, flexibility and hydrophobicity, and its flame retardancy is improved to a certain extent. Among them, the composite additive component in Comparative Example 3 contains only a terminal carboxyl oligoester toughening agent, and its measured wear resistance and hydrophobicity are reduced. The composite additive component in Comparative Example 4 does not contain neodecanoic acid glycidyl ester, and its measured contact angle decreases and hydrophobicity decreases. The composite additive component in Comparative Example 5 does not contain a terminal carboxyl oligoester toughening agent, and its measured curling radius and limiting oxygen index are reduced, and its flexibility and flame retardancy are slightly worse than those of Examples 4-6.
[0072] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0073] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. An impregnated adhesive for pressing decorative paper on a board surface, characterized in that: The invention comprises the following raw materials in parts by weight: 60-75 parts of melamine, 50-80 parts of formaldehyde, 5-15 parts of glutinous rice starch, 1-3 parts of vegetable oleic acid, 10-20 parts of composite additives, and 30-45 parts of deionized water; The composite additive is a mixture of modified nano silicon dioxide and modified nano titanium dioxide in a mass ratio of 3 to 6:1; the modified nano silicon dioxide is an amino nano silicon dioxide grafted with a carboxyl-terminated oligoester toughening agent; the modified nano titanium dioxide is a carboxylated nano titanium dioxide grafted with neodecanoic acid glycidyl ester; The preparation method of the modified nano silicon dioxide comprises the following steps: A. Ultrasonic dispersion of nano-silica in toluene, nitrogen gas for reaction, γ-aminopropyltriethoxysilane and triethylamine, stirring and mixing at 70-90° C., reflux reaction for 9-12 hours, and after the reaction is completed, suction filtration, washing and drying are performed to prepare amino-modified nano-silica; B. Take amino nano-silica and ultrasonically disperse it in N,N-dimethylformamide, add a carboxyl-terminated oligoester toughening agent, reflux at 90-115°C for 5-8h, wash and dry after the reaction is completed, and prepare modified nano-silica; The preparation method of the carboxyl-terminated oligoester toughening agent in step B comprises the following steps: B1, take phenylphosphoryl dichloride and diethylene glycol in a reactor filled with tetrahydrofuran, stir and mix at room temperature, then add triethylamine to react for 4-8 hours, remove the hydrogen chloride produced by the reaction, and after the reaction is completed, filter, rotary evaporate, and dry to prepare a toughening agent intermediate; B2, taking the toughening agent intermediate and glutaric acid into a reactor, placing it at 120-135° C. and stirring for reaction for 6-7 hours, and placing it in a vacuum oven for drying after the reaction is completed to prepare a carboxyl-terminated oligoester toughening agent; The preparation method of the modified nano titanium dioxide comprises the following steps: (1) γ-aminopropyltriethoxysilane and succinic anhydride are placed in N,N-dimethylformamide and stirred at 70-95°C for 2-4 hours to form a mixed solution, nano-titanium dioxide is dispersed in N,N-dimethylformamide, deionized water is added after ultrasonic treatment, and then added to the mixed solution and stirred for 4-5 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to prepare carboxylated nano-titanium dioxide; (2) Dissolve carboxylated nano-titanium dioxide in butyl acetate and disperse by ultrasonication, add triphenylphosphine and hydroquinone, stir and mix at 95-110°C, then add glycidyl neodecanoate to react for 10-14 hours. After the reaction is completed, filter, wash and dry to prepare modified nano-titanium dioxide.
2. The impregnated adhesive for pressing decorative paper on board surface according to claim 1, characterized in that: In the step A, the mass ratio of nano titanium dioxide to γ-aminopropyltriethoxysilane is 3-6:7-10.
3. The impregnated adhesive for pressing decorative paper on board surface according to claim 1, characterized in that: In the step B, the mass ratio of the amino nano-silica to the carboxyl-terminated oligoester toughening agent is 1:1.5-5.
4. The impregnated adhesive for pressing decorative paper on board surface according to claim 1, characterized in that: In the step B1, the mass ratio of phenylphosphoryl dichloride, diethylene glycol and triethylamine is 1:1.1-1.5:1-1.2; and in the step B2, the mass ratio of the toughening agent intermediate and glutaric acid is 1.9-2.5:
1.
5. The impregnated adhesive for pressing decorative paper on board surface according to claim 1, characterized in that: In the step (1), the mass ratio of γ-aminopropyltriethoxysilane, succinic anhydride and nano-titanium dioxide is 2-2.5:0.5-1:2-3.
6. The impregnated adhesive for pressing decorative paper on board surface according to claim 1, characterized in that: In the step (2), the mass ratio of carboxylated nano-titanium dioxide to glycidyl neodecanoate is 1:1.2-3.
7. The method for preparing the impregnated adhesive for pressing decorative paper on board surface according to claim 1, characterized in that: The following steps are involved: S1. Weigh each raw material by weight, mix formaldehyde and deionized water to obtain a mixture A; S2. Adjust the pH value of the mixture A to 8-9.5, raise the temperature to 70-85° C. and keep the temperature for 20-30 min, add melamine, and stir and mix for 20-30 min to obtain a mixture B; S3, adding glutinous rice starch, vegetable oleic acid and composite additives to mixture B, stirring and mixing for 2-4 hours, and preparing the impregnating adhesive for pressing the decorative paper on the board surface.
Citation Information
Patent Citations
Phosphorus-containing polyol, flame-retardant and antistatic polyurethane elastomer prepared by phosphorus-containing polyol and preparation methods of phosphorus-containing polyol and flame-retardant and antistatic polyurethane elastomer
CN109749044A
Toughening biodegradable composition and application thereof
CN113956634A